The pre-process of smart grid algorithm design for network centric air operation during crisis management / Kritsana Sukdee ... [et al]. - Kritsana, Sukdee; Wattanapong, Rakwichian; Watchara, Wongpanyo; Bunyawat, Vichanpol; Chatkaew, Chailuecha (2016)
From the COP21 Paris Agreement 2015, the committees have agreed to reduce the energy consumptions that are produced from coal and fossil. As in effect to the developing countries as similar as the Association of Southeast Asian Nations (ASEAN) because these energy resources are still used widely and high demand for supporting micro-economic level. Furthermore, the coming ASEAN challenge is how to cooperate and sustain the energy assurance against with a disastrous crisis that has created the non-stabilize electrical power has fed into the essential infrastructure of network centric operation (NCO) as well as degrading military operation other than wars (MOOTW) and Humanitarian Assistance and Disaster Relief (HADR) capability. The smart grid is one of the ways out for trouble shooting by effective renewable energy management in Thailand. By the way, the key energy management system (EMS) is a reasonable algorithm which shall be designed to properly recognize the core of the essential demand response and understanding the renewable energy characters are inflexible and unpredictable. The proposed study approach is how to maintain air operational capability, energy assurance, and human assistance during humanitarian catastrophe. The HADR mission requirement, the NCO concept, and the five rings model is mainly integrated into the specific design of smart grid development tool. The results of study indicate energy assurance design model that is able to secure the essential of air operational process failures on the significant NCO concept which is improved by Smart Grid.